The Calculation of EHL of Diagonal Modified Narrow Helical Gears and Film Thickness Measurement - Li Xianwen. et al. (Jixie chuandong)
In this paper, the varying rules of the linear load distribution and the largest stress along the contacting lines are analyzed based on the EHL theory. Applying the method of Newton-Raphson and Newton dowm-hill together, under the assumption of the equal rigid central film thickness, the numerical resolutions along all contacting lines at a time are gained about the helical gears before modification. Based on this, the load and pressure distribution and film thickness of each point along all the contacting lines at a time about the modified belical gears are calculated.On the basis of the laser transmission thohnology used in the reference[4], a sst of data collecting and processing system with a computer was researched. The central film thickness of the helical gears were measured. The measuring results are basically identical to the calculating ones. These show the reasonability and the reliability of the numerical analyzing model established.